2018
DOI: 10.1002/1873-3468.13252
|View full text |Cite
|
Sign up to set email alerts
|

The sialyltransferase ST3Gal3 facilitates the receptivity of the uterine endometrium in vitro and in vivo

Abstract: The receptive uterine endometrium specifically expresses certain glycosyltransferases, and the corresponding oligosaccharides play important roles in accepting the embryo. The sialyltransferase β-galactoside-α2,3-sialyltransferase III (ST3Gal3) is the key enzyme responsible for sialyl Lewis X (sLeX) oligosaccharide biosynthesis, but the expression and function of ST3Gal3 in the receptive endometrium is still elusive. Here, we found that human endometrial tissues at secretory phase expressed a 4-fold higher ST3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 50 publications
0
18
0
Order By: Relevance
“…Sialyltransferase is a biosynthetic enzyme of the sialic acid metabolic pathway mediating the transfer of sialic acid residues to various oligosaccharide chains found on glycoproteins and glycolipids. 32 The proper function of sialyltransferase leads to the formation of sialome. 6 Indeed, sialic acids are vital players in the modulation of cell functions and communications.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Sialyltransferase is a biosynthetic enzyme of the sialic acid metabolic pathway mediating the transfer of sialic acid residues to various oligosaccharide chains found on glycoproteins and glycolipids. 32 The proper function of sialyltransferase leads to the formation of sialome. 6 Indeed, sialic acids are vital players in the modulation of cell functions and communications.…”
Section: Discussionmentioning
confidence: 99%
“…31 Furthermore, it has been reported that enhanced sLeX is associated with a better pregnancy outcome. 32 SLeX on the uterine epithelium has a role in implantation. 32 By carrying out segregation analysis in the family, we found that the mothers (IV.2 and IV.4) were heterozygote for the novel variant.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations